Promoting sustainable land use choices in Indonesia: Experimental evidence on the role of changing mindsets and structural barriers - Miriam Romero; Meike Wollni; Katrin Rudolf; Rosyani Asnawi; Bambang Irawan (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2019)
This study evaluates the effects of two environmental policy instruments on the adoption of native tree planting in oil palm plantations. The first instrument is an information campaign on tree planting in oil palm. The second instrument combines the information campaign with a structural intervention that provides native tree seedlings for free. We implemented a randomized controlled trial in oil palm growing villages in Jambi, Indonesia. Our study addresses the underlying mechanisms of behavioral change, by investigating how the policy instruments shape farmers' perceptions, intentions and actual adoption decisions. The results show that information campaigns and structural interventions can motivate tree planting among smallholder oil palm farmers in Indonesia. While both treatments have a positive and significant effect, the intervention combining information with seedling provision leads to significantly higher adoption rates, indicating that overcoming structural barriers is critical. While changes in perceptions and intentions fully mediate the effect of the information campaign on adoption, they can only partially explain the effect of the combined intervention. Thus, to promote a transition towards more sustainable development pathways, facilitating easy access to critical inputs may be key to motivate adoption among large numbers of potential users.
urn:nbn:de:gbv:7-webdoc-3990-7
Keywords: 330; tree-planting; oil palm; intentions; mediation; Asia